2021
DOI: 10.1021/acs.biomac.0c01290
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Prussian Blue Nanoparticles on Aβ40 Aggregation: β-Sheet Fibril Reduction and Copper Dyshomeostasis Regulation

Abstract: Alzheimer's disease (AD), affecting almost 50 million individuals worldwide, is currently the first cause of dementia. Despite the tremendous research efforts in the last decade, only four supportive or palliative drugs, namely, acetylcholinesterase (AChE) inhibitors donepezil, galantamine, and rivastigmine and the glutamate NMDA receptor antagonist memantine, are currently available. New therapeutic strategies are becoming prominent, such as the direct inhibition of amyloid formation or the regulation of meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…coli. However, the low anti-amyloid activity reported could also be due to an unusually low ability of the compounds to cross the bacterial wall. Although it is unusual, this effect has been observed recently and should not be ruled out …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…coli. However, the low anti-amyloid activity reported could also be due to an unusually low ability of the compounds to cross the bacterial wall. Although it is unusual, this effect has been observed recently and should not be ruled out …”
Section: Discussionmentioning
confidence: 91%
“…Although it is unusual, this effect has been observed recently and should not be ruled out. 41 In conclusion, this research has allowed one to identify interesting lead compounds for the development of new multifunctional molecules useful for AD by virtue of their inhibitory activity toward ChEs, as well as for chelating and antioxidant abilities, low toxicity, and good predicted ADME parameters.…”
Section: ■ Conclusionmentioning
confidence: 91%
“…Therefore, it is unreasonable to monitor Aβ aggregation by ThT dye. It has been demonstrated that CR can specifically bind to the hydrophobic region of amyloid fibrils and exhibit enhanced absorption at 540 nm . Therefore, the CR probe was used to detect the inhibitory potency of MB-CPDs.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous reports, it can act as a nanozyme to scavenge ROS and trap metal ions in its lattice cavities. Recently, Kowalczyk et al studied the dual effects of PB on inhibiting Aβ 1–40 aggregation and chelating Cu 2+ [ 163 ]. They found that PBcould accelerate the nucleation of Aβ 1–40 and facilitate the formation of Aβ 1–40 amorphous aggregates instead of β-sheet fibrils.…”
Section: Nanomaterialsmentioning
confidence: 99%